PENGARUH LEVERAGE DAN FIRM SIZE TERHADAP PENGHINDARAN PAJAK - HARRY BARLI (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2018)
This study aims to find evidence of the influence of Leverage and Firm Size against Avoidance of Taxes. Independent variables used in this study are Leverage and Firm Size. While the dependent variable in this research is Tax Avoidance as measured by Effective Tax Rate (ETR). The type of research used in this study is quantitative data. Source of data used in this research is secondary data. The population in this study is a company Property, Real Estate and Building Construction’s sector listed on the Indonesia Stock Exchange (IDX) during the period 2013-2017. Determination of this research sample using purposive sampling method and get sample of research as many as 34 companies. Hypothesis testing in this study using multiple linear regression method using SPSS version 22. The results of this study indicate that Leverage has an effect on tax evasion. Firm Size has no effect on tax avoidance. While simultaneously shows that Leverage and Firm Size together affect the Tax Avoidance.